PREVALENCE OF DEPRESSION AMONG UNIVERSITY STUDENTS: A CROSS-SECTIONAL STUDY - Nur Zainie Abd Hamid; Shamsinar Ibrahim; Hasyimah Razali (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The prevalence of depression among Malaysians is on the rise. The current state of work and social pressures caused the depression to be declared as the common mental illness among Malaysian by 2020. This mental illness may cause mental health problems among university students due to stress resulted from stressful events in the university environment. Without proper treatment, this can cause disability and even suicide. However, knowing the fact that depression is a treatable illness, therefore, address the illness, and develop preventive strategies in managing mental wellbeing is needed. The primary objective of the present study is to determine the prevalence and severity of depression among university students in Malaysia. This quantitative and cross-sectional study employed 175 undergraduate students from a public university in a rural area. Depression and the severity of the depression were assessed using the validated Patient Health Questionnaire (PHQ-9). Descriptive statistics were used to analyse the data to answer research objectives. Approximately 23.43% of participants experienced depression, which included 1.68% of mild depression, 8.98% of moderate depression, and moderately severe depression, and the remaining 3.37% of severe depression. A considerable proportion of undergraduate students with depression found in this study has called upon the management of the university to pay serious and priority attention to develop psychosocial counselling or targeted intervention for identified depressed students.